TERAPI SENAM NIFAS DAN POLA MAKAN SEHAT SEBAGAI TERAPI PENURUNAN POSTPARTUM BLUES SYNDROME PADA IBU NIFAS - Rini Susanti; Sudarianti; Ruri Aditya Sari (Jurnal Ilmiah Kebidanan Imelda, 2025)
Postpartum blues syndrome is a mild emotional disorder experienced by mothers after giving birth. This disorder can affect the emotional well-being of the mother and her relationship with the baby. Postpartum exercise therapy and a healthy diet are believed to reduce the symptoms of postpartum blues syndrome. This study aims to analyze the effects of postpartum exercise and a healthy diet on the recovery of baby blues syndrome in postpartum mothers. Methods: This study used a quasi-experimental design with a non-equivalent pre- and post-test control group design. The sample consisted of 37 postpartum mothers who were divided into an intervention group (postpartum exercise and a healthy diet) and a control group. Data were collected using the Edinburgh Postnatal Depression Scale (EPDS) questionnaire to measure maternal depression symptoms before and after the intervention. Data analysis was performed using t-tests and multivariate tests. Results: The results showed a significant decrease in depression symptoms in the group that received the intervention compared to the control group (P<0.001). The depression symptoms score decreased by an average of 3.74 in the intervention group that followed postpartum exercise, while a healthy diet contributed to a decrease in depression symptoms with an average reduction of 2.32. Conclusion: Postpartum exercise and a healthy diet can significantly reduce the symptoms of postpartum blues syndrome. Therefore, postpartum exercise and a healthydiet are recommended as routine therapy for postpartum mothers.